A reassessment of the infra-species diversity patterns in the wine-associated Oenococcus oeni - Oviedo-Hernandez, Florencia; Bou-Deleris, Magali; Krieger-Weber, Sibylle; Claisse, Florian; Dereme, Jovnna; Le Marrec, Claire; Claisse, Olivier (Frontiers in Microbiology, 2025)
Oenococcus oeni is the predominant species of lactic acid bacteria in wine, where it carries out malolactic fermentation (MLF), which helps to ensure and preserve the quality of the wine. Today, existing combinations of grape varieties, soil composition, fluctuating climatic parameters, and specific technical processes implemented by wineries lead to incredibly varied wine compositions that pose challenges for spontaneous MLF. Commercial starter cultures have been developed for use as inoculants. However, their effectiveness in ensuring consistent and reliable MLF is also limited in modern wines. The selection process must therefore adapt to these new challenges, which means expanding current portfolios by selecting more robust bacteria from wines that are more varied in terms of grape varieties and chemical constraints. We have assembled a set of 21 wines produced in Europe from different grape varieties, with varying and, in some cases, extreme ethanol contents, total polyphenolic indices, and pH levels. The isolation and MLVA typing of 385 dominant colonies were combined with whole-genome sequencing of 48 representative strains, and we observed several strains with unique accessory genomic content. Different selective pressures led to the formation of groups of genetically related individuals, particularly in white and rosé wines with moderate ethanol content. However, cohabiting strains with contrasting genetic profiles were also observed in some red wines. Our data highlight the complexity of the factors involved in population heterogeneity and raise the possibility that this phenomenon may increase fitness through diversification of strategies or division of labor in specific production environments.